The remainder when 4x3 - 3x2 + 2x - 4 is divided by x+1/2 is -

Let p(x) = 4x3 - 3x2 + 2x - 4  be the given polynomial.

By remainder theorem, when p(x) is divided by (x + 1/2), then required remainder is given by 

p(-1/2).

now, p(x) = 4x3 - 3x2 + 2x - 4

 

  • 2

value of x = -1/2

by substituting its value,

4(-1/2)3 - 3(-1/2)2 + 2(-1/2) - 4

4(-1/8) - 3(1/4) +(-1) - 4

-1/2 - 3/4 -1 - 4

-1/2 -3/4 -5

-2/4 -3/4 -20/4 ......... - LCM = 4

-25/4 IS THE REMAINDER..

  • 1
What are you looking for?